MODEL PEDAGOGI GENRE SEBAGAI STRATEGI PENGEMBANGAN KETERAMPILAN MENULIS: SUATU TINJAUAN TEORETIS DALAM PEMBELAJARAN BAHASA INDONESIA - Wahyu Mustika; Silvia Marni; Wahyudi Rahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing skills are a crucial aspect of Indonesian language learning, requiring students to express ideas logically, structurally, and in accordance with social contexts. However, in practice, writing instruction in schools still faces various challenges, including unsystematic approaches and a lack of understanding of the text types being taught. This article aims to provide a theoretical review of the genre-based pedagogy model as a strategy for developing writing skills in Indonesian language learning. This study employs a literature review method by analyzing academic books, scholarly journals, and relevant curriculum documents. The findings indicate that the genre pedagogy model, rooted in systemic functional linguistics theory, offers a structured writing instruction approach through explicit stages such as building context, modeling text, joint construction, and independent writing. This model not only enhances students’ technical writing abilities but also fosters their awareness of the social functions and structures of various genres. Nonetheless, the effective implementation of this model requires teacher readiness, sufficient training, and curricular support. This study recommends the application of genre pedagogy as an effective alternative strategy in writing instruction and encourages further research to empirically examine its impact in classroom settings.